2002
DOI: 10.1002/cc.66
|View full text |Cite
|
Sign up to set email alerts
|

Campus life for faculty of color: Still strangers after all these years?

Abstract: Minority faculty voice their views on a variety of issues through both quantitative and qualitative data, revealingissues of concern and areas of satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Faculty of color have reported that race and ethnicity influence their reception in the academy (Bower 2002). This is particularly manifested when faculty of color teach courses with multicultural content and when the validity or need for such instruction is challenged by majority students, as is evidenced in the student evaluations of courses and teachers (McGowan 2000;Delgado-Romero et al 2007).…”
Section: The Double Bind: Racism and Sexismmentioning
confidence: 97%
“…Faculty of color have reported that race and ethnicity influence their reception in the academy (Bower 2002). This is particularly manifested when faculty of color teach courses with multicultural content and when the validity or need for such instruction is challenged by majority students, as is evidenced in the student evaluations of courses and teachers (McGowan 2000;Delgado-Romero et al 2007).…”
Section: The Double Bind: Racism and Sexismmentioning
confidence: 97%
“…A number of studies (Astin et al 1997;Bellas 1997;Bower 2002;Bronstein 1993;Dey 1994;Hagedorn 1996;Johnsrud 1993Johnsrud , 2002Laden and Hagedorn 2000;McElrath 1992;Olsen et al 1995;Peluchette 1993;Perna 2001;Thompson and Dey 1998;Turner 2002;Witt and Lovrich 1988), books (Moody 2004;Turner and Myers 2000), monographs (Gainen and Boice 1993;Hagedorn 2000), and two ASHE-ERIC reports (Aguirre 2000;Tack and Patitu 1992) have looked at the experiences, level of job satisfaction, and issues that women and faculty of color face in the academy. Drawing from Kalleberg's theoretical framework of job satisfaction, we discuss the findings from this literature in terms of the six dimensions of job satisfaction.…”
Section: Extension Of Kalleberg's Theory To Women Faculty and Facultymentioning
confidence: 97%
“…One study used a national data set on community college faculty and supplemented it with focus group interviews to discuss what campus life is like for community college faculty members of color (Bower, 2002). Analysis of the survey data indicated little variation in the responses of minority and majority faculty members about such things as workload and perceptions of the institution.…”
Section: Race and Ethnicitymentioning
confidence: 99%